THE INFLUENCE OF WORKLOAD ON PERFORMANCE OF EMPLOYEES AT CORRECTIONAL INSTITUTION CLASS IIA LABUHAN RUKU - Laurent, Joshua; Rachmayanthy, Rachmayanthy (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine the effect of workload on the performance of officers at Class IIA Labuhan Ruku Correctional Facility. This study uses quantitative research methods using a causal design; the data used is through filling out questionnaires given to research respondents. The sampling technique used is probability sampling with random sampling type, with 95 samples. The data from the questionnaire obtained was then analyzed by descriptive analysis tests through simple linear regression analysis, determination tests, and significance tests using the IBM SPSS Statistics 26 application. The conclusion of this study is that there is a positive and significant influence between workload on the performance of officers at the Labuhan Ruku Class IIA Correctional Institution. Keywords: Workload; Employee Performance; Correctional Institution